ADAKAH SAINS ISLAM? - Zuhriyyah Hidayati (CENDEKIA, 2019)
There is an assumption from some scientists, both non-Muslim scientists and Muslim scientists, that the discourse of Islamic science is utopian and unclear. Some scientists even consider that Islamic science does not exist. However, for some activists of Islamic science, Islamic science discourse is a must. Islamic science is a necessity for Muslims today. They continue to strive to discuss Islamic science as an alternative to the fashion science crisis.